2012
DOI: 10.1017/s1431927612000426
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbonate Mineralization: Involvement of Extracellular Polymeric Materials Isolated from Calcifying Bacteria

Abstract: AbstractThis study highlights the role of specific outer bacterial structures, such as the glycocalix, in calcium carbonate crystallizationin vitro. We describe the formation of calcite crystals by extracellular polymeric materials, such as exopolysaccharides (EPS) and capsular polysaccharides (CPS) isolated fromBacillus firmusandNocardia calcarea. Organic matrices were isolated from calcifying bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Extracellular polymeric substances (proteins and/or polysaccharides) can play an important role in biomineralization, regulating and controlling nucleation, and growth of crystal structures (Ercole et al 2012;Kawaguchi and Decho 2002;Li and Gadd 2017a, b;Perri et al 2018;Tourney and Ngwenya 2014). In our study, it was found that the supernatants, or EPS obtained from supernatants, did not exert a significant influence on crystal morphology compared with chemical methods during the formation of cobalt and nickel oxalate.…”
Section: Discussionmentioning
confidence: 58%
“…Extracellular polymeric substances (proteins and/or polysaccharides) can play an important role in biomineralization, regulating and controlling nucleation, and growth of crystal structures (Ercole et al 2012;Kawaguchi and Decho 2002;Li and Gadd 2017a, b;Perri et al 2018;Tourney and Ngwenya 2014). In our study, it was found that the supernatants, or EPS obtained from supernatants, did not exert a significant influence on crystal morphology compared with chemical methods during the formation of cobalt and nickel oxalate.…”
Section: Discussionmentioning
confidence: 58%
“…The higher EPS may be indicative of microbial defense under stressed conditions promoting higher biofilm matrix. The formation of EPS has been found to play a significant role in Calcium carbonate precipitation in a number of previous studies (Bergdale et al, 2012; Ercole et al, 2012). …”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the precipitation rate was also slightly but meaningfully enhanced by the negative-control cells, even though they did not have a detectable CO 2 hydration activity. This result is not surprising, because the E. coli cell surface carries a net negative charge (46), and this can accelerate the rate of CaCO 3 crystal growth, presenting another advantage of using a whole-cell system for CO 2 mineralization (26,47). These results collectively demonstrate that our design concept is useful in developing an efficient catalyst for accelerating CO 2 sequestration in CaCO 3 .…”
Section: Resultsmentioning
confidence: 59%